The Relationship Between Interactive Marketing and Consumer’s Perceived Value. An Analytical Study of The Opinions of a Sample of Workers at The Telecommunications Company in Babylon. - M.Ridha, Bushra Jawad; AL-shammari, Abeer M. Mahdi (International Journal of Psychosocial Rehabilitation, 2020)
The main objective of the study is to find the relationship and influence of interactive marketing with the perceived value of the customer, and the study was conducted at the telecommunications company in Babel City to find out the level of opinions and understanding among workers about the study variables. The main hypotheses of the study were the correlation and influence between the variables and the identification of the effect of the demographic factors of the sample on the dependent variable. The questionnaire was used as a study tool in collecting the required data, and the study reached a fact that is a negative correlation between some dimensions of interactive marketing with the perceived value of the customer with a weak correlation between them, The significance of the effect relationships at the macro level between the two variables was not significant.